PENGEMBANGAN SISTEM BISNIS BERBASIS SYARIAH UNTUK MENDUKUNG STRATEGI PENGEMBANGAN YANG SUSTAINABLE - Maratun Shalihah (IAIN Ambon, 2017)
The financial institutions as mediators of the parties who have excess of funds to the parties who lack of fund so that to be complement each other and serves as the financial intermediary of community. In reality, each institution or organization has several types, namely; first; pure-profit organization, second; quasi-profit organization, third; quasi-non-profit organization and fourth; pure-nonprofit organization. The purpose of first institution type is to make a profit as much as possible in the supply and sale of goods, secondly; aims to make a profit and get other purposes as needed by the owner, thirdly; aims to make profit (surplus) and serve the community, while the last institution aims to improve the community welfare and serve it. The type of organization will continue to face numerous polemics, inequality and disparities occurs today. Therefore, the Islamic economic system is needed as an economic alternative to answer the problems occurs at this time. Key words: Business systems, development, Islamic economics